Investigating the Role of Motivation in Enhancing Learners’ Reading Self-Improvement The Case of First Year EFL Learners at Msila University - Gharsallah Maroua, Bezziane Belkisse (My University, 2020)
This study envisages an investigation about the role of motivation in enhancing learners reading for self-improvement. The aim behind such a research work is to consider teachers‟ and students‟ own perception about reading motivation and how this leads to self-improvement. Reading motivation has received a great deal of research especially for field work which has incited teachers to give it more importance especially how to make learners grow conscious about both intrinsic and extrinsic motivation if they want to reach self-improvement and become strategic readers. To make this study more feasible, both quantitative and qualitative methods, as well as descriptive and argumentative trends were used. This study also went into a deep analysis of the questionnaires to consider the data displayed. The study in its wholeness comprises two questionnaires-one for ten teachers and the other for a population of 120 first year students with a selected sample of 48 students. The questionnaires were piloted, coded and analyzed. The results obtained showed a great support from teachers to learners to be more motivated for self-improvement as active readers. Learners also claimed that motivation is a basic principle in reading for self-improvement. The results obtained from this study will prove positive and very significant for other future researchers.
Keywords: Key Terms : Motivation , Intrinsic Motivation , Extrinsic Motivation , Reading Motivation , Self-improvement .